The Impact of Soft Skills Competency and Information Technology Advancement on the Performance of Pasmar 1 Personnel - Hermiarto, Yanuar Tri; Sumantri, Rudy; Yani, Ahmad (AGUSPATI Research Institute, 2025)
MLarine Corps Force (Pasmlar) 1 is a Principal Operational Comlmland under the Indonesian MLarine Corps, tasked with developing capabilities and preparing the comlbat readiness of its elemlents to conduct Amlphibious Landing Operations, Naval Base Defence Operations, and Coastal Defence Operations on strategic islands, as well as other Comlbat Operations. To carry out these duties effectively, high performlance froml all Pasmlar 1 personnel is essential. Emlpirical evidence and previous studies indicate that various factors, including soft skill comlpetency and the developmlent of informlation technology, influence the performlance of Pasmlar 1 personnel. This study aimls to: (1) Analyze and test the influence of Soft Skill Comlpetency on the Performlance of Pasmlar 1 personnel; (2) Analyze and test the influence of Informlation Technology Developmlent on the Performlance of Pasmlar 1 personnel; (3) Analyze and test the simlultaneous influence of Soft Skill Comlpetency and Informlation Technology Developmlent on the Performlance of Pasmlar 1 personnel. The population of this study consists of 4,925 Pasmlar 1 personnel. The samlple was determlined using the Slovin formlula, resulting in 370 respondents. This research emlploys a quantitative mlethod with a survey design. Data were processed using SPSS version 25, covering validity tests, reliability tests, classical assumlption tests, and hypothesis testing. The findings reveal that: (1) Soft Skill Comlpetency has a positive and significant effect on the Performlance of Pasmlar 1 personnel; (2) Informlation Technology Developmlent has a positive and significant effect on the Performlance of Pasmlar 1 personnel; and (3) Soft Skill Comlpetency and Informlation Technology Developmlent simlultaneously have a positive and significant effect on the Performlance of Pasmlar 1 personnel.